Assessing One Health in Zambia: Necessity, application and operationalisation - Munyeme, Musso; Hamoonga, Raymond; Chitambo, Bertha; Ngoma, Veronica; Maambo, Bhagoos; Nalubamba, King Shimumbo; Knight-Jones, Theodore J.D.; Caron, Alexandre; Richards, Shauna (CAB International, 2024)
“Capacitating One Health in Eastern and Southern Africa (COHESA)” aims at facilitating the ownership, development, adoption, uptake and adaptation of One Health (OH) solutions in Eastern and Southern African region. Further, COHESA developed a set of tools to assess the OH landscape across various countries and the capacity to better approach their OH strategies. The assessment tool used desktop reviews, key informant interviews and focus group discussions. Implemented in Zambia, the data were triangulated through a synthesis process to generate this case. In Zambia, outside the Zambia National Public Health Institute (ZNPHI), no other physical or virtual infrastructure is solely dedicated to OH. The ZNPHI houses the OH physical infrastructure as well as other OH platforms for OH thinking, planning, coordination and working and information sharing and systemic organisation of all multi-sectoral activities concerning OH. It was observed that the OH was mostly accessed by the Ministries responsible for human and animal health. The environment and plant sectors were less represented. It was clear in Zambia that the operationalisation of OH has gone beyond the conceptual level with the production of the National OH Strategic plan and other key documents that guide the implementation of transdisciplinary activities. Additionally, research, innovation and governance around OH were found to be anchored on five thematic areas in Zambia: antimicrobial resistance (AMR); zoonoses control, food safety; toxicology research; and general OH policy issues. The country is moving towards an operational OH system, although there is still need for all disciplines to fully accept the approach.